Sport, social development and peace - Young, Kevin, 1959-; Okada, Chiaki, 1948- (Bingley, U.K. : Emerald, 2014)
This volume is part of the early systematic inquiry into the analysis of sport as a developmental device. The book features an international roster of global experts. The chapters represent three groups: theory and philosophy, empirical research in on-the-ground case studies, and those using circumspection to construct cases regarding evaluation.
Ethical challenges and principle hurdles in sport-for-development work / Simon C. Darnell -- Middle-walkers : negotiating middle ground on the shifting terrain of sport, peace and development / Brian Wilson -- Using postcolonial feminism to investigate cultural difference and neoliberalism in sport, gender and development programming in Uganda / Lyndsay M.C. Hayhurst -- Service-learning : an educational model for sport and community development / Ashleigh M. Huffman, Sarah J. Hillyer -- The contributions of sport to HIV/AIDS awareness / Chiaki Okada -- The role of physical education in the prevention of youth violence : a life skills-based approach in El Salvador / James Mandigo ... [et al.] -- The FIFA World Cup 2010 and its legacy on "sport and development" practices in South African cities / Naofumi Suzuki -- An examination of cross-cultural mentorship in Alberta's future leaders program / Miriam Galipeau, Audrey R. Giles -- From genocide to community sport : a Cambodian life history / Chiaki Okada, Kevin Young -- Where's the "evidence?" Reflecting on monitoring and evaluation within sport-for-development / Ruth Jeanes, Iain Lindsey -- Mega-events, sport legacies and sociologically informed impact assessment / Michael Atkinson, Amanda De Lisio -- Insights and investigations of the social legacies in the 2010 Winter Olympic Games : the Olympic Games impact (OGI) study / Robert VanWynsberghe, Caitlin Pentifallo.
Print version record
Keywords: Sports & Recreation -- Sociology of Sports; Sociology: sport & leisure; Sociology; Sports -- Sociological aspects